Impaired liver regeneration in aged mice can be rescued by silencing Hippo core kinases MST1 and MST2. Issue 1 (9th December 2016) - Loforese, Giulio; Malinka, Thomas; Keogh, Adrian; Baier, Felix; Simillion, Cedric; Montani, Matteo; Halazonetis, Thanos D; Candinas, Daniel; Stroka, Deborah
Abstract: The liver has an intrinsic capacity to regenerate in response to injury or surgical resection. Nevertheless, circumstances in which hepatocytes are unresponsive to proliferative signals result in impaired regeneration and hepatic failure. As the Hippo pathway has a canonical role in the maintenance of liver size, we investigated whether it could serve as a therapeutic target to support regeneration. Using a standard two‐thirds partial hepatectomy (PH) model in young and aged mice, we demonstrate that the Hippo pathway is modulated across the phases of liver regeneration. The activity of the core kinases MST1 and LATS1 increased during the early hypertrophic phase and returned to steady state levels in the proliferative phase, coinciding with activation of YAP1 target genes and hepatocyte proliferation. Moreover, following PH in aged mice, we demonstrate that Hippo signaling is anomalous in non‐regenerating livers. We provide pre‐clinical evidence that silencing the Hippo core kinases MST1 and MST2 with siRNA provokes hepatocyte proliferation in quiescent livers and rescues liver regeneration in aged mice following PH. Our data suggest that targeting the Hippo core kinases MST1/2 has therapeutic potential to improve regeneration in non‐regenerative disorders. Synopsis: Inhibition of the Hippo core kinases MST1 and MST2 with siRNA has the therapeutic potential to improve liver regeneration in age‐related non‐regenerative disorders. Hippo pathway proteins are differentially modulated throughout the quiescent, hypertrophic and proliferative phases of liver regeneration. In aged mice, the modulation of Hippo proteins following partial hepatectomy is altered and liver regeneration is impaired. siRNA encapsulated into liposomes efficiently targets liver parenchymal cells. Deletion of the Hippo core kinases MST1 and MST2 partially restores liver regeneration in a non‐regenerative aged mouse model, suggesting them as promising candidates as pharmacological targets to treat non‐regenerative disorders. Abstract : Inhibition of the Hippo core kinases MST1 and MST2 with siRNA has the therapeutic potential to improve liver regeneration in age‐related non‐regenerative disorders.